Validity Of Statement Of Sale and Purchase Of Land Above a Seal In Transfer Of Land Rights - Koedho Mahan Yirangkat; Johan Erwin Isharyanto (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
Problems arise when the seller and buyer have died while the land that is the object of the sale and purchase is controlled by a third party. The formulation of the problem is as follows: 1) How is the validity of a land sale and purchase statement above the seal in the transfer of land rights? 2) What are the legal considerations of the panel of judges in the Pati District Court Decision Case Number 7 /Pdt.G/2023/PN. Pti.? 3) What are the legal consequences for the parties to the Pati District Court Decision Case Number 7/Pdt.G/2023/PN. Pti ? This study used a normative legal research approach. The data analysis used was a qualitative approach to secondary data as the main and primary data as supporting data. The results of the study show that the validity of the land sale and purchase statement letter above the seal in the transfer of land rights can be seen from the fulfillment of two requirements; general and special requirements. The legal consideration of the panel of judges in the Pati District Court Decision Case Number 7/Pdt.G/2023/PN.Pti. is that the Defendant's actions in controlling a plot of land recorded in the Village Book C Number 870, Plot Number 24 Class D1 covering an area of 270 M2 located in RT 002 RW 005 Tunjungrejo Village, Margoyoso Sub-District, Pati Regency are against the law. The legal consequences for the parties to the Pati District Court Decision Case Number 7/Pdt.G/2023/PN.Pti is that the Plaintiff has the right to control a plot of land as recorded in the Village Record Number 870, Plot Number 24 Class DI Area 270 M2, located in Rt 002 Rw 005 Tunjungrejo Village, Margoyoso Sub-District, Pati Regency, and the Defendant and the third party were ordered to vacate the land belonging to Ah Djumadi or his heirs which was the object of the dispute.